2022
DOI: 10.1186/s12958-022-01033-x
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in Folliculogenesis and potential modifiers to improve fertility outcomes - A narrative review

Abstract: Reproductive aging is characterized by a decline in oocyte quantity and quality, which is directly associated with a decline in reproductive potential, as well as poorer reproductive success and obstetrical outcomes. As women delay childbearing, understanding the mechanisms of ovarian aging and follicular depletion have become increasingly more relevant. Age-related meiotic errors in oocytes are well established. In addition, it is also important to understand how intraovarian regulators change with aging and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 292 publications
0
20
0
Order By: Relevance
“…Mitochondrial impairment has been pointed out as an aging hallmark [ 3 , 17 , 21 , 31 , 36 ], and its involvement in oocyte deterioration in AMA women has already been described [ 37 , 38 ]. Abnormalities in mitochondrial ultrastructure, dynamics and integrity, metabolism, and mtDNA mutations and deletions [ 17 ] have been studied in follicular cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondrial impairment has been pointed out as an aging hallmark [ 3 , 17 , 21 , 31 , 36 ], and its involvement in oocyte deterioration in AMA women has already been described [ 37 , 38 ]. Abnormalities in mitochondrial ultrastructure, dynamics and integrity, metabolism, and mtDNA mutations and deletions [ 17 ] have been studied in follicular cells.…”
Section: Discussionmentioning
confidence: 99%
“…The delaying of motherhood, induced by an increase in educational, employment, and career opportunities [ 1 , 2 ], is one of the factors responsible for an age-related decline in fertility in several contexts due to a decrease in oocyte quantity and quality [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Higher FF levels of 25-hydroxyvitamin D were shown to be substantially related to greater clinical pregnancy and implantation rates in a study examining infertile women undergoing IVF [168]. The number of mature oocytes retrieved and the success rates of oocyte fertilization in patients undergoing IVF were favorably connected with blood VD levels in various prospective studies [65]. The same study's multivariable logistic regression analysis found FF levels of VD as an independent predictor of an IVF cycle's success after correcting for age, BMI, ethnicity, and the number of embryos transferred (Esencan et al, 2022).…”
Section: Vitamin Dmentioning
confidence: 96%
“…VEGF levels in follicular fluid rise with age in both natural and in vitro fertilization (IVF) cycles [33,[62][63][64][65]. This aging-related rise in VEGF levels could be a result of selective gonadotropin elevation in older reproductive-age women, a compensatory response to follicular hypoxia, and a decrease in energy synthesis in the presence of impaired mitochondrial function [21].…”
Section: Vascular Agingmentioning
confidence: 99%
“…The mechanisms suggested in the etiopathogenesis are a decrease in the initial ovarian reserve and an increase in the rate of ovarian follicle atresia. It has been suggested that the reproductive aging in humans is part of the same biological process based on oxidative stress-induced DNA damage and apoptosis (2,3).…”
Section: Introductionmentioning
confidence: 99%